Involvement of α2‐antiplasmin in dendritic growth of hippocampal neurons. (22nd May 2013) - Kawashita, Eri; Kanno, Yosuke; Asayama, Haruka; Okada, Kiyotaka; Ueshima, Shigeru; Matsuo, Osamu; Matsuno, Hiroyuki
Abstract The α2‐Antiplasmin (α2AP) protein is known as a principal physiological inhibitor of plasmin, but we previously demonstrated that it acts as a regulatory factor for cellular functions independent of plasmin. α2AP is highly expressed in the hippocampus, suggesting a potential role for α2AP in hippocampal neuronal functions. However, the role for α2AP was unclear. This study is the first to investigate the involvement of α2AP in the dendritic growth of hippocampal neurons. The expression of microtubule‐associated protein 2, which contributes to neurite initiation and neuronal growth, was lower in the neurons from α2AP−/− mice than in the neurons from α2AP+/+ mice. Exogenous treatment with α2AP enhanced the microtubule‐associated protein 2 expression, dendritic growth and filopodia formation in the neurons. This study also elucidated the mechanism underlying the α2AP‐induced dendritic growth. Aprotinin, another plasmin inhibitor, had little effect on the dendritic growth of neurons, and α2AP induced its expression in the neurons from plaminogen−/− mice. The activation of p38 MAPK was involved in the α2AP‐induced dendritic growth. Therefore, our findings suggest that α2AP induces dendritic growth in hippocampal neurons through p38 MAPK activation, independent of plasmin, providing new insights into the role of α2AP in the CNS.